The framing of LGBT-related issues in Malaysian online newspapers - Loke, Jasmine Hui Xia (2022)
The Lesbian, Gay, Bisexual and Transgender (LGBT) in Malaysia are criminalized and regarded as taboo. Due to limited studies on the subject matter, this research aimed to explore the framing of LGBT-related issues in Malaysian online newspapers, namely The Star Online and MalaysiaKini. The research objectives include to explore how extensively LGBT-related issues were covered by the newspapers, to examine the news frames reported and to investigate the valence of the articles published by the newspapers in their coverage of LGBT-related issues. The content analysis method was employed in this research. Findings showed that LGBT-linked issues were given less visibility in the newspapers. The most published news type is straight news with over half (51.4%) of the articles covering LGBT issues in Malaysia while the remaining articles were related to LGBT events in other nations. The top news frames utilized were “deviance” and “equal rights” with most of the articles portrayed in a positive or neutral tone. Suggestions include investigating LGBT framing in non-English-language newspapers and studying Malaysians’ perceptions on LGBT issues in the media to shed light on the level of support, acceptance, tolerance and rejection towards LGBT issues among the Malaysian society.